Strategi Meningkatkan Keterampilan Menyimak Murid dengan Interactive Flat Panel (IFP) Implementasi Teaching By Principles: An Interactive Approach To Language - Farida Nugrahani; Muhammad Nurrohim; Sukiman; Arlandi Dwi Kuncoro; Uut Arif Rahman; Chera Widiastuti; Maya Sari, Ria Indra Maya Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Douglas Brown's dimensions divide learners into children, adolescents, and adults. Language skills are essential for all individuals at every age level. The first language skill humans acquire is listening. The purpose of this study is to determine strategies for improving students' listening skills, particularly at the elementary school level, after the use of interactive flat panel (IFP) media. This research was inspired by Douglas Brown's book, chapters six and sixteen. The study used literature review and interviews. The results, described in a qualitative descriptive manner, indicate that the use of IFP can improve children's listening skills.